Prima Tourism Education Development Strategy Selemak Village - Qaedina Tio Athira; Rulianda Purnomo Wibowo; Meilita Tryana Sembiring (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The decline in the number of visitors to Prima Wisata Edukasi over the years has resulted in the village's income not meeting the expected targets. The main issues in this study are how to formulate an effective business strategy to increase village income through tourism management and how to implement this strategy to increase visitor numbers. This study aims to develop an appropriate business strategy and analyze its implementation at Prima Wisata Edukasi. The research employs a qualitative descriptive approach to gain an in-depth understanding of the dynamics in tourism management. Informants were selected using purposive sampling and included the Head of Mantar Village, the Chairman of BUMDES, community leaders, and tourists. Data were collected through in-depth interviews and direct observations, and then analyzed thematically. The findings reveal that the success of tourism destination management is influenced by interconnected internal and external factors. Strengths such as unique tourism offerings, diverse attractions, adequate facilities, affordable prices, and strategic location serve as key potentials supported by social media promotion. However, weaknesses include limited human resource competencies, insufficient promotion, and suboptimal facility maintenance procedures. Opportunities from family tourism trends and government support should be maximized, while challenges such as limited access, disaster risks, and intense competition require mitigation strategies. Based on these findings, several implementation strategies are recommended, including strengthening educational partnerships, improving human resource competencies, optimizing promotions, and establishing facility maintenance procedures to enhance the competitiveness and sustainability of Prima Wisata Edukasi.